Treatment effects of “PowerScope” fixed functional appliance – a clinical study - Anirudh Kalra; Vinit Swami; Veera Bhosale (Folia Medica, 2021)
Aim: To study the skeletal, dental effects and evaluate the soft tissue changes with PowerScope-fixed functional appliance in class II malocclusion.Materials and methods: This clinical study was carried out where a total of 10 growing (CVMS 3 and 4) Class II Division 1 malocclusion patients, indicated for treatment with fixed functional appliance were allocated based on specific inclusion criteria. PowerScope (American Orthodontics) was used as the fixed functional appliance. Skeletal, dental and soft tissue effects of the appliance with various angular and linear parameters on a digital lateral cephalogram were evaluated for all 10 participants. Records were collected before the insertion of PowerScope appliance (T0) and after 5 months, during the appliance removal (T1). All participants were treated with 0.018ʺ×0.025ʺ MBT (3M Unitek) prescription. Statistical analysis was performed using a paired t-test to compare individual mean changes for each treatment category. Results: Statistically significant changes were seen in skeletal parameters such as forward positioning of the mandible with an increase in SNB angle and N perpendicular-Pogonion distance, the class II jaw base relationship improved with reduction in ANB angle and Wits appraisal. Significant changes were observed in dental parameters such as forward positioning of mandibular incisors, maxillary molar distalization and intrusion with reduction in overbite and overjet respectively. In the soft tissue, a significant improvement in facial profile was seen due to an increase in labiomental angle.Conclusions: The results of this study have shown that statistically significant changes in skeletal, dental and soft tissue parameters